Analisis Framing dalam Berita Kasus Pencabulan Murid SD di Bekasi pada Media Online Kompas.com dan Detik.com - Lusi Rahmawati; Hendra Setiawan (Departement of Mathematics Education, 2023)
A piece of news about a teacher who sexually abused his own student continues to be a hot topic of conversation. Teacher molestation of students is an abnormal activity that can violate a teacher’s code of ethics. This reporting cannot be separated from the framing carried out by news writers. The existence of a framing formed by a journalist becomes an idea or ideas that can generate a lot of public opinion. This study uses the Zhongdang Pan and Gerald M. Kociski framing analysis model by focusing on four structural dimensions of news text as a framing device, including: (1) syntactic structure, (2) script structure, (3) thematic structure, (4) rhetorical structure. The purpose of this study is to get an overview and understanding of how the online media Kompas.com and Detik.com frame reporting on cases of sexual abuse of elementary school students against students in Bekasi.